Au cœur des services : les larmes au travail - Angelo Soares (Perspectives Interdisciplinaires sur le Travail et la Santé)
For a long time it was assumed that emotions may be left at the door of the organisations. This excessively simplifies the complexity and heterogeneity of work, leading to an underestimation of the effects of work on health. Our objective is to understand one particular form of the expression of workers’ emotions : crying at work. In order to understand this question, we use a qualitative approach with workers in different jobs in the service sector in Montreal. Crying at work is linked to an excess of emotional labour and the impossibility of its achievement. Differences between male and female crying, at least at work, may be explained not only by a gendered socialization of individuals, but also by the sexual division of emotional labour. This imposes an emotional overload on women, since a more intensive management of emotions is demanded of them at work.